Ethanol administration during retrieval, but not consolidation, influences the relative use of multiple memory systems - Daniela Gonzalez; Eva Lorenz; Devon Patel; Kah-Chung Leong (Addiction Neuroscience, 2022)
The mammalian brain consists of two competing memory systems: the hippocampus-dependent cognitive memory system and dorsal striatum-dependent stimulus-response memory system, which can be influenced by drugs of abuse. The formation and retrieval of cognitive and stimulus-response memories can be acquired using a place or response strategy, respectively. The purpose of the present study was to investigate the effects of ethanol on the relative use of the cognitive and stimulus-response memory systems and its effects on retrieval and consolidation processes. The dual-solution water maze task offers a behavioral paradigm to determine the relative preference of memory systems in rats. Male Sprague-Dawley rats were trained over two days on the dual-solution water maze task and were tested on the third day of the paradigm. In Experiment 1, ethanol was administered 30 min before the test day probe trial. In Experiment 2, ethanol was administered immediately after each training session. Results from Experiment 1 showed that ethanol exposure prior to test biases animals towards preferential use of the response strategy to complete the task. In Experiment 2, post-training ethanol exposure did not bias animals towards the use of either strategy on test day. The present study indicates that ethanol biases the relative use of multiple memory systems towards the use of the stimulus-response memory system through interactions with the retrieval process but not the consolidation process. Alcohol's effect on preferential use of the stimulus-response memory system has important implications for the understanding of alcohol use disorder, general addiction, and memory function.